ANALISIS RISIKO PRODUK MAKANAN HALAL DALAM MENJAMIN KUALITAS PRODUK MAKANAN DI INDUSTRI KECIL DAN MENENGAH - Nofriani Fajrah; Nilda Tri Putri; Anggia Arista; Sri Zetli (Prosiding, 2026)
Indonesia ranks third in the Islamic Economy Indicator Score according to the State of the Global Islamic Economy Report 2024/25. In line with this achievement, the Indonesian government, through the Badan Penyelenggara Jaminan Produk Halal (BPJPH), ensures that food products are certified as halal. This policy requires all food business manufacturers to obtain halal certification for their products. The objective of this study is to analyse potential risks in halal food products among Small and Medium Enterprises (SMEs) to ensure the quality and integrity of halal food products. This study employed a quantitative research approach and was conducted through a case study of food SMEs in Batam City, Indonesia. The Failure Mode and Effects Analysis (FMEA) method was utilised to identify risk factors and analyse their causes, thereby preventing potential contamination that could compromise product quality and halal compliance. Primary data were collected through interviews and direct observations of production processes, while secondary data were obtained from production reports. The findings of this study indicate that 15 risks were identified in the production process. The highest risk factor was found at R04 with a Risk Priority Number (RPN) of 75, which obtained a level 1 rating and fell into the 'Very High' risk category. This risk pertains to the preparation area for the main raw ingredients for making doughnuts, which is conducted on the floor, thus posing a potential for contamination from dirt/dust. As for the recommended suggestion, it is to provide a separate storage area for the preparation zone, distinct from the dough-mixing area, so that dirt, dust, or other contaminants do not contaminate and enter the doughnut dough. This way, the halal integrity and quality of the doughnuts can be maintained